Corporate Board Diversity and Financial Performance: The Nigerian Insurance Sector’s Perspective - Moses, Gbarato, Ledum (Growth, 2020)
The presence of appropriate gender diversity, board size and board composition does not only promote favourable organizational ambience but also offers meaningful upsurge in the financial position of an organization relatively. It is on this premise that prompted the essence to examine the relationship between corporate board diversity and financial performance of insurance companies in Nigeria for the period 2014 to 2018. Secondary data from Cornerstone Insurance Plc. and Lasaco Assurance Plc. were employed in the study. Using the Panel least Square regression technique, the results reveal that gender diversity, board size and board composition exert insignificant influence on profit before tax as the measure of financial performance. However, while gender diversity exerts negative influence, board size and board composition exert positive influences on profit before tax of insurance companies. The study concludes that employment of appropriate number of directors and also in suitable composition as board members have positive effect on the financial performance of insurance firms. Therefore, the study recommended among others, that: appropriate ratio of executive to independent non-executive directors should be maintained among board members for better decision-making at the interest of all stakeholders. Also, the ratio of gender diversity (female to male directors) should be increased as the role of women in resource management cannot be relegated to the background especially in financial performance of insurance companies.